Give the graph of each solution. Show the line f(x) = x as dashed. To see an example, type "inverse of f(x) = -2x + 1" into Wolfram Alpha.

Find the inverse: \(f(x) = x + 2\)

\(f^{-1}(x) = x - 2\)

Find the inverse: \(f(x) = 3x - 4\)

\(f^{-1}(x) = \dfrac{x + 4}{3}\)

Find the inverse: \(f(x) = \dfrac{1}{2}x - 5\)

\(f^{-1}(x) = 2x + 10\)

Find the inverse: \(f(x) = -x + 4\)

\(f^{-1}(x) = -x + 4\)
Finding inverse functions: linear

Find the inverse: \(f(x) = -2x - 1\)

\(f^{-1}(x) = \dfrac{-x - 1}{2}\)
Finding inverse functions: linear

Find the inverse: \(f(x) = \dfrac{2}{3}x + 2\)

\(f^{-1}(x) = 3x - 3\)

Find the inverse: \(f(x) = 5x\)

\(f^{-1}(x) = \dfrac{x}{5}\)

Find the inverse: \(f(x) = \dfrac{-5}{3}x - 8\)

\(f^{-1}(x) = \dfrac{-3x - 24}{5}\)

Step by Step process to find the inverse of a linear function

Brian McLogan

Find the inverse:

\(f(x) = \dfrac{-5}{3}x - 8\)
Find the inverse: \(f(x) = 6x - 2\)

\(f^{-1}(x) = \dfrac{1}{6}x + \dfrac{1}{3}\)

Find the inverse: \(f(x) = \dfrac{1}{4}x\)

\(f^{-1}(x) = 4x\)

Find the inverse: \(f(x) = 3x + 1\)

\(f^{-1}(x) = \dfrac{x - 1}{3}\)

Find the inverse: \(f(x) = \dfrac{2}{3}x - 5\)

\(f^{-1}(x) = \dfrac{3}{2}x + \dfrac{15}{2}\)

Find the inverse: \(f(x) = \dfrac{-1}{5}x + 2\)

\(f^{-1}(x) = -5x + 10\)

Find the inverse: \(f(x) = \dfrac{-2}{5}x + 2\)

\(f^{-1}(x) = \dfrac{-5}{2}x + 5\)

Find the inverse: \(f(x) = \dfrac{2}{3}x - 1\)

\(f^{-1}(x) = \dfrac{3}{2}x + \dfrac{3}{2}\)

Find the inverse: \(f(x) = \dfrac{1}{6}x\)

\(f^{-1}(x) = 6x\)

Find the inverse: \(f(x) = 2x - 7\)

\(f^{-1}(x) = \dfrac{1}{2}x + \dfrac{7}{2}\)

Find the inverse: \(f(x) = 3x - 1\)

\(f^{-1}(x) = \dfrac{1}{3}x + \dfrac{1}{3}\)

Find the inverse: \(f(x) = 3x - 6\)

\(f^{-1}(x) = \dfrac{x + 6}{3}\)